Islam jawa: kesalehan normatif versus kebatinan/ Mark R. Woodward ; penerjemah Hairus Salim HS, penyunting Amirudun, Nuruddin. - MARK R. WOODWARD; Hairus Salim HS; Amirudun; Nuruddin (LKIS, 2012)
xxii, 410,[4]hlm.; 20cm.(3 eks)